Unveiling the Anomalous Effect of Foreign Investment on Yogyakarta’s Regional Economy: A Spatial Durbin Model Approach - Rinusara, Novita Mukti (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
Foreign investment's effect on the economy does not need to be doubted and debated, but still, it needs to be proven in real life. This research uses 4 regencies and 1 city of the Special Region of Yogyakarta Province data with the dependent variable is gross regional domestic product (GRDP), representing the regional economy of each regency/city. The model estimated using OLS and the Spatial Durbin Model, this research is trying to confirm the effect of foreign investment on the GRDP. The results show foreign investment negative effect on the GRDP in both OLS and the Spatial Durbin Model’s direct and indirect effect.